2014
DOI: 10.1093/ije/dyu002
|View full text |Cite
|
Sign up to set email alerts
|

Cohort Profile: French hospital database on HIV (FHDH-ANRS CO4)

Abstract: The French Hospital Database on HIV (FHDH) is a hospital-based multicentre open cohort with inclusions ongoing since 1989. The research objectives focus mainly on mid- and long-term clinical outcomes and therapeutic strategies, as well as severe AIDS and non-AIDS morbidities, and public health issues relative to HIV infection. FHDH also serves to describe HIV-infected patients receiving hospital care in France. FHDH includes data on more than 120,000 HIV-infected patients from 70 French general or university h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
46
1

Year Published

2015
2015
2022
2022

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 73 publications
(50 citation statements)
references
References 37 publications
3
46
1
Order By: Relevance
“…The demographic and medical characteristics of the participants in our study were in line with those reported in the national French hospital database (FHDH) and the national French VESPA2 survey (Dray-Spira et al, 2013;Mary-Krause et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…The demographic and medical characteristics of the participants in our study were in line with those reported in the national French hospital database (FHDH) and the national French VESPA2 survey (Dray-Spira et al, 2013;Mary-Krause et al, 2014).…”
Section: Discussionsupporting
confidence: 80%
“…This first estimate for this population in France is in agreement with findings from other low-burden countries: 9.4% in the Swiss cohort, as measured by Mantoux >5 mm (13), and 14.6% in Spain according to IGRAs (14). To rule out recruitment biases, we assessed the representativeness of our study population by comparing them to the ARTnaive HIV-infected patients followed within the French Hospital Database on HIV (FHDH) cohort (16). To rule out recruitment biases, we assessed the representativeness of our study population by comparing them to the ARTnaive HIV-infected patients followed within the French Hospital Database on HIV (FHDH) cohort (16).…”
Section: Discussionsupporting
confidence: 80%
“…28 The FHDH ANRS-CO4 uses a unique encrypted identifier that is generated by an algorithm based on the first name, the last name, and the date of birth. A 1:2 (patient:control) ratio was chosen, as this was the highest number of controls we were able to select; we were able to find two HIV-uninfected counterparts with these criteria for almost all PLHIV, but rarely three.…”
Section: Methodsmentioning
confidence: 99%